2007
DOI: 10.1143/jjap.46.l1061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser-Plasma X-Ray Irradiation on Crystallization of Amorphous Silicon Film by Excimer Laser Annealing

Abstract: We consider the classical Arnold example of diffusion with two equal parameters. Such a system has two-dimensional partially hyperbolic invariant tori. We mainly focus on the tori whose ratio of frequencies is the golden mean. We present formal approximations of the three-dimensional invariant manifolds associated with this torus and numerical globalization of these manifolds. This allows one to obtain the splitting (of separatrices) vector and to compute its Fourier components. It is apparent that the Melniko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…The difference in the activation energy between the furnace annealing and the soft X-ray irradiation, namely, 0.12 eV, may be related to the effect of soft X-ray irradiation. We have reported that a crystal-like region, called the quasi-nucleus, is formed by electron excitation and atomic movement with soft X-ray irradiation of amorphous Si [13]- [16]. It seems that the metastable state (crystal-like region) in the damage region introduced by B ion implantation was achieved by soft Xray irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the activation energy between the furnace annealing and the soft X-ray irradiation, namely, 0.12 eV, may be related to the effect of soft X-ray irradiation. We have reported that a crystal-like region, called the quasi-nucleus, is formed by electron excitation and atomic movement with soft X-ray irradiation of amorphous Si [13]- [16]. It seems that the metastable state (crystal-like region) in the damage region introduced by B ion implantation was achieved by soft Xray irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The coating designs are simply G/(ML) 2 /air, G/(ML) 5 M/air, and G/(ML) 20 M/air, for AR, BS and HR coatings, respectively, where M is quarterwave layer Al 2 O 3 , L is quarterwave layer SiO 2 , and G is substrate fused silica (30 mm diameter, 3 mm thickness). The substrates were ultrasonic cleaned under class 1000 clean room conditions.…”
Section: Preparation and Characterization Of Multilayer Coatingsmentioning
confidence: 99%
“…Excimer laser systems have been widely used in many fields, e.g., medical science 1,2) , micromachining 3,4) , laser annealing 5,6) , and deposition of thin film 7,8) . However, many applications suffer from the limited resistance of optical components against intense laser radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Matsuo et al found that laser plasma soft X-ray irradiation before excimer laser annealing (ELA) reduced the critical energy density for the initiation of crystallisation of amorphous silicon films. 5 The results of their study will enable us to realize a low-temperature process for ELA crystallisation. However, an intense, high average-power soft X-ray beam for irradiation is required to realize such application.…”
Section: Introductionmentioning
confidence: 97%